Heidegger on Being and Acting From Principles to Anarchy (Indiana University Press, 1990)
What happens when "thinking" no longer secures a rational foundation for knowledge and "acting" no longer means conforming one's daily enterprises, public and private, to that foundation? In his brilliant deconstructionist analysis Reiner Schürmann provides a comprehensive interpretation of Heidegger's thinking from the perspective of this question. Focusing on the relationship between theory and practice in an era in which metaphysical rationality has come to an end, Schürmann explicates an economy of presencing in which thinking can no longer be called upon to legitimize praxis by measuring it against some enduring principle or archē. Thinking and acting, he concludes, can then become an-archic.